2021
DOI: 10.1111/jfpp.15228
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of inulin and fructooligosaccharide supplementation on the growth and survival of Lactobacillus casei in model sugar systems

Abstract: Lactobacilli generally used in the production of fermented food products such as yogurt, sauerkraut, pickles, and wine also function as a probiotic culture benefiting humans and animals by improving gut microbial balance. Lactobacilli are known to derive metabolic energy from homofermentative or heterofermentative carbohydrate fermentation to accomplish its complex nutritional requirements (Didari et al., 2014; Makarova et al., 2006). Among many strains and species of lactobacilli which are used commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…A positive growth effect of 1% inulin of L. plantarum ST16 Pa has been reported by da Silva Sabo et al [43]. A similar dose-dependent effect of inulin and FOS was reported by Parhi et al [35] on the growth of L. casei. Moreover, Munoz et al [44] reported that CFU increased with increasing FOS (1%, 2%) concentration for L. casei LE8, but CFU decreased with increasing FOS (5%) concentration for L. plantarum LE27.…”
Section: Growth Studysupporting
confidence: 81%
See 2 more Smart Citations
“…A positive growth effect of 1% inulin of L. plantarum ST16 Pa has been reported by da Silva Sabo et al [43]. A similar dose-dependent effect of inulin and FOS was reported by Parhi et al [35] on the growth of L. casei. Moreover, Munoz et al [44] reported that CFU increased with increasing FOS (1%, 2%) concentration for L. casei LE8, but CFU decreased with increasing FOS (5%) concentration for L. plantarum LE27.…”
Section: Growth Studysupporting
confidence: 81%
“…The survival assay was performed according to Bevilacqua et al [39]; modified by Parhi et al [35]. MRS broth (20 mL) was dispensed in Schott bottles and inoculated at 5% w/v with L. plantarum (Figure 1).…”
Section: Survival Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics can promote the utilization of FOS by intestinal microbiota ( 40 ). Parhi et al ( 41 ) show that Lactobacillus casei can promote the utilization of FOS by fecal microbes, thereby altering the intestinal microbial composition. The results of the population trial showed that Bifidobacterium longum W11 combined with FOS synbiotics could improve the defecation frequency and reduce the colonic transport time of constipated patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modified Bifidobacterium broth (250 lL) was dispensed in a 96-well plate in an anaerobic chamber, and the plate was then incubated and measured simultaneously inside a TECAN SparkÒ10 M microplate reader (TECAN, Gro ¨dig, Austria) at 37 °C for 24 h. Microbial growth was monitored by measuring the absorbance at OD 600 every 60 min intervals, with 15 s auto-shaking at 1440 rpm before each measurement. Growth Index (%) was calculated using the equation according to Bevilacqua et al (2016), modified by Parhi et al (2021a):…”
Section: Growth Curve Assaymentioning
confidence: 99%